Responsibility of TNI Soldiers Who Commit Lesbian, Gay, Bisexual and Transgender Crimes According to the Military Legal System - Yudi Pranoto Atmojo; Hamdan Azhar Siregar (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Sexual relations do not only occur between different genders, but can also occur between individuals of the same sex. This problem in Indonesia often causes differences of opinion between those who support and those who oppose. It is undeniable that in the military environment there are also deviations in sexual orientation carried out by the perpetrator who is a TNI soldier in the verdict of the Military Court II-08 Jakarta Number 212-K / PM II-08AD / XI / 2020. Finding, analyzing, and explaining the viewpoint of military law on the existence of LGBT in the military environment was the goal of the study. The ruling of the Military Court II-08 Jakarta Number 212-K / PM II-08AD / XI / 2020 clarifies the criminal culpability of TNI soldiers who engage in Lesbian, Gay, Bisexual, and Transgender (LGBT) actions. Legal theory, criminal responsibility theory, and the theory of legal certainty are the frameworks utilized. Normative juridical research is the methodology employed. Based on the findings of this study, the military's official stance on the presence of LGBT individuals in the military has been firmly established by highlighting the ban on LGBT individuals as stated in the TNI Commander's Telegram Letter Number ST/398/2009. As stated in Telegram Letter Number ST/1648/2019 from the TNI Commander, LGBT is one of the behaviors that soldiers are not to engage in since it goes against official orders or is not in line with soldier life norms. Furthermore, it is highlighted in the Supreme Court Circular (SEMA) Number 10 of 2020, in letter D number 1, that disobeying the TNI Commander's Telegram Letter Number ST/398/2009 dated July 22, 2009 and the TNI Commander's Telegram Letter Number ST/1648/2019 dated October 22, 2019, which forbid TNI soldiers from engaging in immoral acts with members of the same sex (Homosexual/Lesbian), can be seen as a violation of official orders under the provisions of Article 103 Paragraph (1) of the Criminal Code. In accordance with the processes or mechanisms for resolving LGBT crimes guided by Law Number 31 of 1997 concerning Military Justice, TNI soldiers found guilty of LGBT acts in the Jakarta Military Court II-08 Number 212-K/PM II-08AD/XI/2020 will face prosecution, sentencing, and criminal penalties in accordance with the specific legal regulations based on Military Criminal Law.